Merge over move and the Extended Projection Principle: MOM and the EPP Revisited - Castillo, Juan Carlos; Drury, John E.; Grohmann, Kleanthes (IBERIA: An International Journal of Theoretical Linguistics, 2010)
A class of proposals are examined that aim to avoid problems that arise in various instantiations of the ‘Merge over Move’ (MOM) cost-of-operation distinction. It is concluded that while the mechanisms introduced there exhibit independently interesting features, they subtract substantially from the interest of the MOM economy of derivation explanations. The removal of an assumption will then be considered that makes the core cases involving there-constructions a problem to begin with: that non-finite T must host a specifier position (checking an EPP/D-feature). Denying the existence of such features removes the problem that the MOM distinction was introduced to solve, allowing the core cases of associate-movement vs. expletive-insertion to arise as a case of true optionality. Consequences for other phenomena are examined and the proposal is found to be consistent with much recent research investigating these phenomena.